Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies